Minimally invasive treatments revitalizing facial skin - a case study - Matthews-Brzozowska, Teresa; Łącka, Monika; Kawałkiewicz, Weronika; Mojs, Ewa; Kubisz, Leszek (Journal of Medical Science, 2018)
The increasing longevity of today’s societies has created a considerable need for the revitalization of facial skin undergoing the ageing processes. It is important to undertake preventive measures and start therapy when the first signs of ageing appear. This makes it possible to achieve a satisfactory effect while using minimally invasive procedures. Among them, treatments based on autologous preparations occupy a significant place, such as those using stem cells and concentrated growth factors (CGF), which have recently been introduced on the Polish market. Such a procedure was used on the patient described in this paper. In a series of instrumental studies, after three administrations of CGF-Harmony, improved values for the measurements reflecting skin elasticity were obtained, which was confirmed by instrumental examination of the skin using a Cutometer Dual MPA 580. Instrumental analysis of the mechanical parameters of facial skin makes it possible to demonstrate the effectiveness of treatment in the field of facial aesthetic medicine.
Keywords: face; revitalization; CD34 stem cells; concentrated growth factors (CGF)